Studies on Pathological Alterations and Diseases of Nervous System in Small Ruminants (Indian Journal of Veterinary Pathology, 2025)
Neurological disorders in small ruminants present a significant challenge to livestock health and productivity, yet they remain comparatively underexplored. This study aimed to characterize the pathological alterations in the central nervous system (CNS) of goats and sheep exhibiting neurological signs. A total of 68 brain samples (44 goats; 24 sheep) were collected during post-mortem examinations. Gross lesions included meningeal congestion, cerebral and cerebellar hemorrhages, encephalomalacia and the presence of Oestrus ovis larvae. Histopathological evaluation revealed inflammatory lesions (vasculitis, meningitis, neuronophagia), reactive changes (chromatolysis, gliosis, satellitosis), vascular alterations (congestion, edema) and degenerative changes (spongiosis, axonal degeneration). Disease specific lesions consistent with listeriosis and rabies were also observed. Bacteriological culture and PCR confirmed Listeria monocytogenes and Escherichia coli as causative agents in select cases. The findings underscore the diagnostic value of integrating gross pathology, histopathology, microbiology and molecular techniques for the comprehensive identification and understanding of CNS disorders in small ruminants.